Methanotrophic community abundance and composition in plateau soils with different plant species and plantation ways - Dai, Yu; Wu, Zhen; Xie, Shuguang; Yong Liu (APPLIED MICROBIOLOGY AND BIOTECHNOLOGY, 2015)
Aerobic methane-oxidizing bacteria (MOB) play an important role in mitigating the methane emission in soil ecosystems to the atmosphere. However, the impact of plant species and plantation ways on the distribution of MOB remains unclear. The present study investigated MOB abundance and structure in plateau soils with different plant species and plantation ways (natural and managed). Soils were collected from unmanaged wild grassland and naturally forested sites, and managed farmland and afforested sites. A large variation in MOB abundance and structure was found in these studied soils. In addition, both type I MOB (Methylocaldum) and type II MOB (Methylocystis) were detected in these soils, while type II MOB usually outnumbered type I MOB. The distribution of soil MOB community was found to be collectively regulated by plantation way, plant species, the altitude of sampling site, and soil properties.